Population dynamics and reproductive features of the Amazon River prawn Macrobrachium amazonicum (Heller, 1862) in Neotropical reservoirs under drought events - Paschoal, Lucas Rezende Penido [UNESP]; Zara, Fernando José [UNESP] (My University, 2024)
Here, we describe population and reproductive dynamics of four populations of Macrobrachium amazonicum in reservoirs during drought events. Additionally, we analyze possible phenotypic changes in this species promoted by fish predation. Two populations had a large-size phenotype (with large body proportions and morphotypes in males) while a small-size phenotype (with reduced sizes and no morphotypes) was found in the two other populations. Overall, females were larger than males and there were varying sex ratios among the four studied populations. All populations had bimodal or polymodal patterns in their monthly size-class frequency, suggesting a seasonal influence and a potentially great capacity of these populations to adapt to adverse environmental conditions. No major changes were found in the patterns of sex ratio, recruitment, frequency of (larger) male morphotypes and female ovarian development stages during drought events. Macrobrachium amazonicum is a resilient species and undergoes continuous reproduction. Females with immature ovaries were predominant in all populations, performing multiple spawns and exhibiting rapid ovarian development cycles. In males, the initial morphotype (TC-translucent claw) was predominant in populations with a social hierarchy. Males of dominant morphotypes (GC1 and GC2-green claw 1 and 2) use more energy to carry out and maintain metabolic processes, which could probably one of the explanations why their number in populations are limited. We did not find any clear evidence that fish predation affected phenotypes, suggesting that phenotypic plasticity could be more related to intrinsic factors, which would have to be further investigated.
Keywords: Caridea; drought; phenotypes; reproduction; synergistic events